2017
DOI: 10.1017/s1751731117000209
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value and anthelmintic effect of sainfoin pellets fed to experimentally infected growing rabbits

Abstract: Alternative strategies to synthetic chemical drugs are needed in livestock and are a key issue in organic farming today. This study aimed at examining the potentialities of sainfoin, a legume rich in condensed tannins, as a nutraceutical that combines nutritive and antiparasitic effects in rabbits. To test the effect of infection with a helminth (I: infected groups; NI: not infected groups) and the effect of substituting 40% of the alfalfa in a control diet (C) with sainfoin (diet S), four groups of 16 weaned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
(33 reference statements)
2
7
0
Order By: Relevance
“…It is suspected that proteins are bound with tannins in the range of intestinal pH and might therefore be less available for digestive processes; these results agreed with those reported by 14 .…”
Section: Resultssupporting
confidence: 90%
“…It is suspected that proteins are bound with tannins in the range of intestinal pH and might therefore be less available for digestive processes; these results agreed with those reported by 14 .…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, the AH effect may also depend on the animal species. For example, the consumption of pellets containing sainfoin did not reduce fecal egg counts, worm burdens, or female worm fecundity in rabbits (Legendre et al 2017) or horses (Collas et al 2018), while the same type of pellets led to in vivo AH activity in sheep (Gaudin et al 2016).…”
Section: How Viable Is the Use Of The In Vitro Nutraceutical Evaluatimentioning
confidence: 98%
“…Yet, along with the difference in CP concentration between GRF and LEG, differences in their protein digestibility and contents of essential amino acids, such as methionine, cysteine, lysine and threonine, must also be considered (Xiccato and Trocino, 2010). The concentration of condensed tannins in sainfoin may limit protein digestibility, as Legendre et al (2017) observed recently for conventionally reared rabbits.…”
Section: Discussionmentioning
confidence: 99%